The reinvention of a peripheral neighbourhood in Lisbon: Reflections on urban art, ethnography and public policy - Raposo, O. (Arts and ethnography in a contemporary world: From learning to social participation, 2019)
In Quinta do Mocho, a neighborhood on the outskirts of Lisbon, young residents have started working with the city council as community guides for an urban art project. In a few years, the neighborhood, which had until that point been represented as a synonym for violence and decadence, became an open-air “art gallery” visited by thousands of tourists. In light of this new context, it is important to discover how the neighborhood’s residents are dealing with these changes. Based on an ethnographic accompaniment of the guided tours and daily lives of the young guides, this chapter aims to contribute to a reflection on art, ethnography, stigma, segregation and public policies.